Meeting standards through integrated curriculum - Drake, Susan M.; Burns, Rebecca Crawford (Alexandria, Va. Association for Supervision and Curriculum Development, 2004)
Many schools are under pressure to meet new standards of learning mistakenly believe that they must adopt a narrow curriculum that imposes strict boundaries on what students are taught. In this book, Susan M. Drake and Rebecca C. Burns address this issue by offering strategies for synchronizing standards across the disciplines. At the heart of the book is the KNOW/DO/BE framework, which teachers can use to ensure a curriculum that is both rigorous and relevant to K-12 students at all stages of proficiency. Among other things, this comprehensive framework allows teachers to: (1) Map curriculum; (2) Scan and cluster standards; (3) Develop assessments and guiding questions; (4) Align integrated instructional strategies and assessments. Though the authors draw much of their data from research on integration, their focus is on analyzing the real-life experiences of teachers who have successfully integrated their curricula in the service of accountability. The many benefits of this approach that the authors explore include dates of homework completion among students. By combining case studies with a wealth of supporting research, Meeting Standards Through Integrated Curriculum offers teachers a user-friendly system for meeting standards while advancing broad-based learning. The book is organized into the following 12 Chapters: (1) "What Is Integrated Curriculum?"; (2) "Why Integrate the Curriculum in an Era of Accountability?"; (3) "Creating the KNOW/DO/BE Bridge"; (4) "Using Standards to Integrate the Curriculum"; (5) "Aligning Assessment and Instruction with the KNOW/DO/BE Bridge"; (6) "A Template for Planning Interdisciplinary Curriculum"; (7) "Castles, Kings ... and Standards One Classroom's Experience with Integrated Curriculum"; (8) "Making Connections: A Multidisciplinary Model"; (9) "A Mission to Transform Education: Newsome Park Elementary School"; (10) "The Alpha Program: Students as Standards-Based Curriculum Designers"; (11) "Questions and Answers"; and (12) "The Future of Integrated Curriculum: Stilling the Pendulum". The following are appended: (1) Interdisciplinary Curriculum Template for the Medieval Times Unit; (2) Making Connections Template and Rubric; and (3) Alpha Program Planning Sheet.
Includes bibliographical references and index.
Keywords: Education -- Curricula -- United States; Interdisciplinary approach in education -- United States; Education -- Standards -- United States